All roads lead to the vacuole—autophagic transport as part of the endomembrane trafficking network in plants. (19th November 2017) - Kalinowska, Kamila; Isono, Erika
Abstract : Autophagic transport is part of the endomembrane trafficking system and factors such as ESCRTs, RAB GTPases, retromer, HOPS and SNAREs are important for proper autophagy in plants and other organisms. Abstract: Plants regulate their development and response to the changing environment by sensing and interpreting environmental signals. Intracellular trafficking pathways including endocytic-, vacuolar-, and autophagic trafficking are important for the various aspects of responses in plants. Studies in the last decade have shown that the autophagic transport pathway uses common key components of endomembrane trafficking as well as specific regulators. A number of factors previously described for their function in endosomal trafficking have been discovered to be involved in the regulation of autophagy in plants. These include conserved endocytic machineries, such as the endosomal sorting complex required for transport (ESCRT), subunits of the HOPS and exocyst complexes, SNAREs, and RAB GTPases as well as plant-specific proteins. Defects in these factors have been shown to cause impairment of autophagosome formation, transport, fusion, and degradation, suggesting crosstalk between autophagy and other intracellular trafficking processes. In this review, we focus mainly on possible functions of endosomal trafficking components in autophagy.